Comparative Life Cycle Analysis of Hybrid and Conventional Drive Vehicles in Various Driving Conditions - Emilia M. Szumska (Communications - Scientific letters of the University of Zilina, 2021)
Growing environmental concern prompts vehicle users to search for cleaner and ecological transport modes. Many consumers and organizations have decided to replace conventional diesel or gasoline powered vehicles with alternative drive or alternative-powered vehicles. Operating conditions may have a heavy influence on the operating parameters of vehicles, such as: airpollution emission, energy consumption and fuel consumption. This paper presents a comparative analysis of the life cycle of conventional and hybrid drive vehicles in various driving conditions. The presented LCA results show that replacing a conventional diesel or gasoline vehicle with a hybrid electric drive vehicle results in approximately 40 % lower total lifetime air-pollutant emissions than those of conventional drive vehicles in urban driving conditions.